Incorporating Aboriginal women's voices in improving care and reducing risk for women with diabetes in pregnancy - A phenomenological study - Anna J Wood; Sian Graham; Jacqueline A Boyle; Beverley Marcusson-Rababi; Shonada Anderson; Christine Connors; Harold D McIntyre; Louise Maple-Brown; Renae Kirkham (BMC, 2021)
Abstract Background There is a high burden of gestational diabetes (GDM) and type 2 diabetes in pregnancy for Aboriginal and Torres Strait Islander women. Postpartum diabetes programs have the potential to prevent recurrent GDM and improve management of type 2 diabetes. However, data on such programs are limited, particularly in the Indigenous context. We aimed to explore Aboriginal Australian women's and health providers' preferences for a program to prevent and improve diabetes after pregnancy. Methods A phenomenological methodology underpinned semi-structured in-depth interviews with eleven Aboriginal women and seven health professionals across the Northern Territory from October 2019- February 2020. Interviews were analysed using an inductive analysis framework to address the barriers and enablers of proposed diabetes prevention programs identified by participants. Results Identified structural barriers to lifestyle change included: food insecurity, persuasive marketing of unhealthy food options, lack of facilities and cultural inappropriateness of previous programs. Enablers to lifestyle change included: a strong link between a healthy lifestyle and connection with Country, family and community. Suggested strategies to improve lifestyle included: co-designed cooking classes or a community kitchen, team sports and structural change (targeting the social determinants of health). Lifestyle change was preferred over metformin to prevent and manage diabetes after pregnancy by participants and health care providers. Conclusions We recommend individual level programs be designed alongside policies that address systemic inequalities. A postpartum lifestyle program should be co-designed with community members and grounded in Aboriginal conceptions of health to adequality address the health disparities experienced by Aboriginal people in remote communities.